2015
DOI: 10.4209/aaqr.2013.07.0253
|View full text |Cite
|
Sign up to set email alerts
|

Size-Differentiated Chemical Composition of Re-Suspended Soil Dust from the Desert Southwest United States

Abstract: As part of the Desert Southwest Coarse Particulate Matter Study which characterized the composition of fine and coarse particulate matter in Pinal County, AZ during 2010-2011, several source samples were collected from several different soil types to assist in source apportionment analysis of the study results. Soil types included native desert soils, agricultural soils (crop farming), dirt-road material adjacent to agricultural areas, paved road dusts, dirt road material from within and adjacent to a cattle f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…Relative to Al, average ratios of K, Ca, and Fe were 0.48, 0.88, and 0.56, respectively. These ratios are similar to those found in resuspended PM 10 soil collected in the study region (Upadhyay et al, 2012) as well as resuspended PM 10 soil collected in the U.S.-Mexico border region (Watson and Chow, 2001;Chow et al, 2004) and near Owens (Dry) Lake, California (Rojo et al, 2008), and slightly higher than those found in upper continental crust (Rudnick and Geo, 2003). These results suggest that crustal material is likely regional in nature.…”
Section: Mass and Meteorologysupporting
confidence: 84%
See 1 more Smart Citation
“…Relative to Al, average ratios of K, Ca, and Fe were 0.48, 0.88, and 0.56, respectively. These ratios are similar to those found in resuspended PM 10 soil collected in the study region (Upadhyay et al, 2012) as well as resuspended PM 10 soil collected in the U.S.-Mexico border region (Watson and Chow, 2001;Chow et al, 2004) and near Owens (Dry) Lake, California (Rojo et al, 2008), and slightly higher than those found in upper continental crust (Rudnick and Geo, 2003). These results suggest that crustal material is likely regional in nature.…”
Section: Mass and Meteorologysupporting
confidence: 84%
“…The remaining sampler was used to collect blanks, other colocated samples, and samples for quality assurance/quality control and instrument precision determination. More detailed information about blank and quality assurance and control measures can be found in the study overview (Clements et al, 2012).…”
Section: Sample Collectionmentioning
confidence: 99%
“…EC abundances were lowest in NS (0.004% ± 0.009%) while Inorganic ions fraction were most abundant in URD (1.49% ± 1.06%). These results agreed well with studies in other regions of the world [15][16][17]19], and indicated that human activity-related factors, such as vehicle exhaust, can greatly modify the chemical characteristics of entrained crustal material from sources affected by these activities.…”
Section: Contributions Of the Major Componentssupporting
confidence: 90%
“…The major sources of dust pollution include suspension of soil, agriculture related activities, road dust, vehicular exhaust, power plants, construction activities, brick kilns and cement factories etc. (Karanasiou et al, 2014;Upadhyay et al, 2015). In addition, transboundary and long range transport also contributes a significant amount of atmospheric dust in the south Asian region (Begum et al, 2011).…”
Section: Introductionmentioning
confidence: 99%